Paclitaxel-loaded Polymersomes for Enhanced Intraperitoneal Chemotherapy - Simón-Gracia, Lorena (Mol Cancer Ther, 2016)
Peritoneal carcinomatosis is present in more than 60% of gastric cancer, 40% of ovarian cancer, and 35% of colon cancer patients. It is the second most common cause of cancer mortality, with a median survival of 1–3 months. Cytoreductive surgery combined with intraperitoneal chemotherapy is the current clinical treatment, but achieving curative drug accumulation and penetration in peritoneal carcinomatosis lesions remains an unresolved challenge. Here we employed flexible and pH-sensitive polymersomes for payload delivery to peritoneal gastric (MKN-45P) and colon (CT26) carcinoma in mice. Polymersomes were loaded with Paclitaxel® and in vitro drug release was studied as a function of pH and time. Paclitaxel-loaded polymersomes remained stable in aqueous solution at neutral pH for up to four months. In cell viability assay on cultured cancer cell lines (MKN-45P, SKOV3, CT26), Paclitaxel-loaded polymersomes were more toxic than free drug or albumin-bound Paclitaxel (Abraxane(®)). Intraperitoneally administered fluorescent polymersomes accumulated in malignant lesions, and immunofluorescence revealed intense signal inside tumors with no detectable signal in control organs. A dual targeting of tumors was observed: direct (circulation independent) penetration, and systemic, blood vessel-associated accumulation. Finally, we evaluated preclinical antitumor efficacy of polymersomes-paclitaxel in treatment of MKN-45P disseminated gastric carcinoma using a total dose of 7 mg/kg. Experimental therapy with polymersome-Paclitaxel improved the therapeutic index of drug over Paclitaxel-Cremophor and Abraxane(®), as evaluated by intraperitoneal tumor burden and number of metastatic nodules. Our findings underline the potential utility of the polymersome platform for delivery of drugs and imaging agents to peritoneal carcinomatosis lesions.